2021
DOI: 10.3389/fcell.2021.716461
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk of Focal Adhesion-Related Gene Defines Prognosis and the Immune Microenvironment in Gastric Cancer

Abstract: Background: Focal adhesion, as the intermediary between tumor cells and extracellular matrix communication, plays a variety of roles in tumor invasion, migration, and drug resistance. However, the potential role of focal adhesion-related genes in the microenvironment, immune cell infiltration, and drug sensitivity of gastric cancer (GC) has not yet been revealed.Methods: The genetic and transcriptional perspectives of focal adhesion-related genes were systematically analyzed. From a genetic perspective, the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…ECM-receptor interaction pathway is identified as an important pathway associated with the progression of GC ( Hu and Chen, 2012 ). Focal adhesion plays a key role in regulating cell survival, and proliferation, migration, and invasion of GC cells ( Mao et al, 2021 ). The PI3K-Akt signaling pathway plays an important role in the development and progression of GC ( Matsuoka and Yashiro, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…ECM-receptor interaction pathway is identified as an important pathway associated with the progression of GC ( Hu and Chen, 2012 ). Focal adhesion plays a key role in regulating cell survival, and proliferation, migration, and invasion of GC cells ( Mao et al, 2021 ). The PI3K-Akt signaling pathway plays an important role in the development and progression of GC ( Matsuoka and Yashiro, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the above conclusions, the results of enrichment analysis, such as response to hypoxia and decreased oxygen, and HIF-1 signaling pathway, indicated that this module's key metabolic genes had tight association with hypoxia process. Previous studies have demonstrated that focal adhesions, as mediators of tumor cells and the extracellular matrix, are vital in various ways within tumor migration, invasion, and drug resistance (35). The results of GO enrichment analysis, such as focal adhesion and cell-substrate junction, indicated that the key metabolic genes in the module may be closely associated with metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…ECM-receptor interaction was reported as an important pathway linked with the progression of GC [60] . Focal adhesion was identified as a key player in regulating cell survival and proliferation, migration, and invasion of GC cells [61] . The PI3K-Akt signaling pathway was known to play an important role in the development and progression of GC [62] .…”
Section: Discussionmentioning
confidence: 99%